Aplicación de técnicas de programación neurolingüística (PNL) al personal de ventas de Comercializadora Darpa S.A. de la ciudad de Loja para el año 2014 - Palacio González, José Alberto (2014)
This research work purpose is to implement NLP as a tool to influence the sales on Darpa Distributor S.A. in the city of Loja, by applying certain techniques of neurolinguistic programming, this work demonstrate an endless number of opportunities to develop commercially as well as personally, this led to a more functional and technical management in the client-seller relationship where we could accomplish: happier customers, effective negotiations and increment on sales mainly in the third quarter. NLP served not only to strengthen a win-win relationship between the company and its customers but also to make the business more profitable, I greatly improved internal and external communication in the company and is especially NLP as a non-rigid option but very flexible to suit different market conditions and serves as a tool for analysis and reflection and mainly for decision making.